Impact of climate change on coffee in Uganda. Lessons from a case study on Arabica coffee in the Rwenzori Mountains - Jassogne, Laurence T.P.; Asten, Piet J.A. van; Läderach, Peter R.D. (Oxfam, 2013)
Coffee is a major cash crop in Uganda accounting for about 20 30% of foreign exchange earnings. Smallholder farmers whose average farm sizes range from 0.5 to 2.5 ha produce 90% of Uganda s coffee. The livelihoods of these smallholder coffee farmers are very vulnerable and studies have shown that climate change can increase this vulnerability even further. This project aims at understanding the potential impact of climate change on coffee-based livelihoods. We focused this study on Arabica coffee (Coffea Arabica), since this requires a rather cool tropical climate that is only found in high altitude areas. In Uganda, Arabica is predominantly found above 1400 m and this altitude threshold would move up hundreds of meters if temperatures rise.